PENDIDIKAN ANAK MENURUT ZAKIAH DARADJAT - Firda Pratiwi; Adelina Nur Hidayah; Nelvi Khairani; Siti Nur Jannah (POTENSIA: Jurnal Kependidikan Islam, 2018)
Education is process that leads people to the good life and the uplifting of humanity in accordance with the basic capabilities (nature) and the his teaching ability (external influences). True education is that provides the opportunity for openness to influences from the outside world and the development of the student themselves. The purpose of  education is expected to from the persoality of a person into human beings with the pattern of taqwa to Allah SWT. Where the purpose of education is essentially that can humans in line with the incident. And aims to gain the solvation of the world and the hereafter. With the exixtence of education is expected to produce human beings who have a good personality in outword and inward who are able to devote charity and deeds to seek pleasure Allah. Education in the family has a strategic role and very decivise achievement of the quality of human resources. Implementation of family education is not just arolw as a routine and natural executor but acst as a responsible manager in laying a founation, weight direction and patterns of child life